The Science of Linguistics: Papers in Honour of Ștefan Oltean - FARKAS, Imola-Agnes; TODEA, Adriana (Presa Universitară Clujeană, 2020)
Professor Ștefan Oltean is celebrating his 70th birthday this July. This special anniversary has occasioned this Festschrift, which we dedicate to him as we were both privileged to have him as our university professor, mentor and scientific advisor of our doctoral dissertations, an experience that has had a long-lasting influence on our careers. The contributors to this volume – colleagues, friends, former and present PhD students – have gathered to celebrate this special occasion.